Causal relationship between atherosclerosis and inflammatory bowel disease risk: a two-sample Mendelian randomization study - Wenjuan Guo; Na Peng; Shiyu Du (Thrombosis Journal)
Abstract Objective This study was to evaluate the causal associations of atherosclerosis with the risk of inflammatory bowel disease (IBD), and its subtypes [ulcerative colitis (UC) and Crohn’s disease (CD)]: a two-sample Mendelian randomization study. Materials and methods Single nucleotide polymorphism (SNPs) associated with atherosclerosis including CPAmax, CPSmax, brachial-femoral pulse wave velocity (bfPWV), coronary atherosclerosis, cerebral atherosclerosis, peripheral atherosclerosis, coronary artery disease (CAD) and ischemic stroke (IS) were identified from previous genome-wide association studies (GWAS). SNPs were strictly selected to fulfill the MR assumptions. The causal links between atherosclerosis and IBD were evaluated using inverse-variance weighted (IVW) as the primary method. Leave-one-out analysis was utilized to evaluate whether the outcomes were attributable to any individual SNP correlated to sex hormones. The estimates were subjected to odds ratio (OR) and 95% confidence interval (CI). Results The results of IVW revealed that coronary atherosclerosis had causal association with increased risk of CD (OR = 1.162, 95%CI: 1.031–1.311). The causal association was also observed in IS with CD (OR = 1.376, 95%CI: 1.011–1.873) and UC (OR = 1.508, 95%CI: 1.153–1.971). Leave-one-out analysis indicated that no single SNP can affect the associations of CAD with IBD, CD, and UC, coronary atherosclerosis with CD, as well as IC with CD and UC. Conclusions Coronary atherosclerosis was causally related to CD, and IS had causal relationship with CD and UC. The finding might provide evidence for future exploration of the etiology for IBD.